Contribution toward comprehension of contact angle values on single polydimethylsiloxane and poly(ethylene oxide) polymer networks - Bouteau, Murielle (Langmuir : the ACS journal of surfaces and colloids, 2010)
The large application ranges of polydimethylsiloxane (PDMS) and poly(ethylene oxide) (PEO) based materials justify the importance of controlling polymer surface properties including morphology and wettability behavior. However, it appears that the reported contact angle values of PDMS surfaces show significant scattering which cannot always be interpreted in terms of sole chemical data. In addition, few values are reported concerning pure PEO surfaces, since the polymer generally swells in the presence of water. Thus, in order to correlate surface properties with sample preparation, several single PDMS and PEO polymer networks were synthesized with varying cross-linkers and different cross-linking densities. First, the sample surface topography was systematically analyzed by atomic force microscopy (AFM). It was proven that the removal process of the polymer film from the mold plays a significant role in surface topography according to the vitreous or rubbery state of the given polymer network at room temperature irrespective of mold surface treatment. AFM-scale smooth surfaces can be obtained for all the samples by removing them systematically from the mold at a temperature below the α-relaxation temperature. Dynamic water contact angles were then measured and the values analyzed as a function of cross-linker nature and cross-linking density